Comparison of the effects of host-associated (autochthonous) and commercial probiotics on immune responses, growth parameters and intestinal microbiota of Caspian whitefish (Rutilus frisii kutum) fry - Hoseinifar, Seyed Hossein; Hoseini, Seyyed Morteza; Taheri Mirghaed, Ali; Ghelichpour, Melika; Shirzad-Aski, Hesamaddin; Van Doan, Hien; El-Haroun, Ehab; Safari, Roghieh; Khanzadeh, Majid (Frontiers in Marine Science, 2024)
This study investigates the effects of host-associated probiotic (HAP) vs commercial probiotic (CP) on the growth performance, antioxidant defence and immunity of Caspian whitefish fry. Three hundred whitefish fry (1.15 ± 0.03 g) were randomly divided into five treatments in triplicate. Treatments included feeding with the control group (zero), P. acidilactici as a commercial probiotic (CP) at 6 × 10 8 CFU g -1 , and HA Pediococcus pentosaceus at 10 6 , 10 7 and 10 8 CFU g -1 for eight weeks. Dietary HAP and CP did not have significant effects on growth indices compared to the control group (P > 0.05). However, HAP at 10 7 and 10 8 CFU g -1 and CP significantly increased protein in whitefish carcasses compared to the control group (P < 0.05).Different levels of HAP and CP had a significant effect on whole-body extract (WBE) lysozyme (LZM) activity (P < 0.05). HAP treatment significantly increased WBE ACH50 and bactericidal activity compared to the control and CP group (P < 0.05). Also, in the case of mucosal immune response, different levels of HAP could significantly increase LZM, total immunoglobulin (Ig),agglutination titer, protease and alkaline phosphatase activity compared to the control group (P < 0.05). Whitefish fed HAP showed a significant increase in the activity of WBE antioxidant parameters (SOD, CAT and GPx) compared to the control group (P < 0.05). Also, feeding withHAP could significantly increase autochthonous LAB levels compared control group (P < 0.05); while the total count of intestinal heterotrophic bacteria was not affected (P > 0.05). Overall, the present study showed HA Pediococcus pentosaceus can be considered as beneficial feed additive for whitefish.